THE LANGUAGE OF REGULATIONS: EXPLORING THE RIGHT TO RESTITUTION FOR CHILD VICTIMS OF SEXUAL CRIMES - Mardiwel, Mardiwel; Suhartono, Slamet; Setyorini, Erny Herlin; Mangesti, Yovita Arie (Ensiklopedia Research and Community Service Review, 2024)
Abstract: Children's rights are also part of the most fundamental human rights. Generally, protection for children is represented by children who come into contact with the law. From the Child Protection Law emphasizes that legal protection for children is the state's obligation, including for child victims of sexual violence. Every child who becomes a victim of a crime has the right to restitution. The purpose of research is to analyze and find the essence and concept of restitution for child victims of sexual violence based on the principle of justice. The type of research is normative legal using normative legal case studies, with approaches including legislative, philosophical, conceptual, case, and comparative approaches. The collection of legal materials is conducted by reviewing literature sources. The analysis of legal materials in this normative research consists of reading regulations, journals, and other references.Result shows that the essence of providing restitution for child victims of sexual violence based on the principle of justice is that children are vulnerable victims for whom the state is obligated to advocate for their rights in the form of restitution, making it easily accessible and beneficial for child victims. The concept of providing restitution for child victims of sexual violence emphasizes the need to reinforce the Sexual Crimes Law for children in fulfilling the right to restitution and must be clearly regulated through policies that facilitate child victims of sexual violence in applying for restitution.Keywords: restitution, children, sexual violence, principle of justice